2016
DOI: 10.1182/blood-2015-02-628164
|View full text |Cite
|
Sign up to set email alerts
|

AID-associated DNA repair pathways regulate malignant transformation in a murine model of BCL6-driven diffuse large B-cell lymphoma

Abstract: • The combined effects of AIDassociated base excision and MMR delay the development of BCL6-driven DLBCL.• UNG single deficiency prevents the development of BCL6-driven DLBCL.Somatic hypermutation and class-switch recombination of the immunoglobulin (Ig) genes occur in germinal center (GC) B cells and are initiated through deamination of cytidine to uracil by activation-induced cytidine deaminase (AID). Resulting uracil-guanine mismatches are processed by uracil DNA glycosylase (UNG)-mediated base-excision rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 60 publications
2
26
0
Order By: Relevance
“…Thus, our results predict that UNG deficiency could in fact protect from GC-derived B cell lymphoma. Indeed, a recent study found that UNG deficiency protected Iμ-HABcl6 mice from DLBCL ( Gu et al, 2016 ), which was previously shown to be AID dependent in that mouse model ( Pasqualucci et al, 2008 ). In contrast, Iμ-HABcl6 Ung −/− Msh2 −/− and Iμσ-HABcl6 Msh2 −/− mice developed DLBCL faster than Iμ-HABcl6 mice ( Gu et al, 2016 ).…”
Section: Discussionmentioning
confidence: 89%
“…Thus, our results predict that UNG deficiency could in fact protect from GC-derived B cell lymphoma. Indeed, a recent study found that UNG deficiency protected Iμ-HABcl6 mice from DLBCL ( Gu et al, 2016 ), which was previously shown to be AID dependent in that mouse model ( Pasqualucci et al, 2008 ). In contrast, Iμ-HABcl6 Ung −/− Msh2 −/− and Iμσ-HABcl6 Msh2 −/− mice developed DLBCL faster than Iμ-HABcl6 mice ( Gu et al, 2016 ).…”
Section: Discussionmentioning
confidence: 89%
“…DLBCL is a heterogeneous disease characterized by high levels of genomic instability (Barlow et al, 2013), and activation of DNA damage repair pathways, including the activation of nucleotide excision DNA repair (NER) and DNA damage response kinases (Shaheen et al, 2011;Gu et al, 2015). Studies have shown that inhibition of the process of DNA damage repair, such as inhibitors of kinase WEE1, could effectively prevent the progress of DLBCL (Knittel et al, 2018;Jong et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of mutation frequency and hotspot enrichment was performed as previously described [3,25]. Statistical comparison of mutation frequencies was performed using Fisher's exact test (one-tailed), and the significance of AID hotspot and CpG motif enrichment was assessed using the binomial test.…”
Section: Data Analysis and Statisticsmentioning
confidence: 99%